Efficacy and Safety of Dapagliflozin by Baseline Glycemic Status: A Prespecified Analysis From the DAPA-CKD Trial - Persson, Frederik; Rossing, Peter; Vart, Priya; Chertow, Glenn M.; Hou, Fan Fan; Jongs, Niels; McMurray, John J.V.; Correa-Rotter, Ricardo; Bajaj, Harpreet S.; Stefansson, Bergur V.; Toto, Robert D.; Langkilde, Anna Maria; et al. (Diabetes care, 2021)
OBJECTIVE The Dapagliflozin and Prevention of Adverse outcomes in Chronic Kidney Disease (DAPA-CKD) study demonstrated risk reduction for kidney and cardiovascular outcomes with dapagliflozin versus placebo in participants with chronic kidney disease (CKD) with and without diabetes. We compared outcomes according to baseline glycemic status. RESEARCH DESIGN AND METHODS We enrolled participants with CKD, estimated glomerular filtration rate (eGFR) 25–75 mL/min/1.73 m2, and urinary albumin-to-creatinine ratio 200–5,000 mg/g. The primary composite end point was sustained eGFR decline ≥50%, end-stage kidney disease, or kidney or cardiovascular death. RESULTS Of 4,304 participants, 738 had normoglycemia, 660 had prediabetes, and 2,906 had type 2 diabetes. The effect of dapagliflozin on the primary outcome was consistent (P for interaction = 0.19) in normoglycemia (hazard ratio [HR] 0.62 [95% CI 0.39, 1.01]), prediabetes (HR 0.37 [0.21, 0.66]), and type 2 diabetes (HR 0.64 [0.52, 0.79]). We found no evidence for effect modification on any outcome. Adverse events were similar, with no major hypoglycemia or ketoacidosis in participants with normoglycemia or prediabetes. CONCLUSIONS Dapagliflozin safely reduced kidney and cardiovascular events independent of baseline glycemic status.